PO 139 - PERIOPERATÓRIO DA DREPANOCITOSE: O QUE HÁ AINDA POR DESCOBRIR? - Nogueira Pinto, Catarina; Rodrigues Pereira, Cláudia; Soares, Maria (Journal of the Portuguese Society of Anesthesiology, 2023)
x